A Classification of a Liturgy's Use of Scripture: A Proposal. (September 2019) - Olver, Matthew S. C.
The relationship between scripture and Christian liturgy is one that was discussed and assumed in much of the liturgical and ecumenical literature in the twentieth century. The majority of that work focused on the use of the Bible within liturgical rites in general and not within the text of specific liturgical rites. This article is a constructive proposal of a comprehensive taxonomy to describe all the possible ways that a liturgical text can appropriate scripture as a source. Such attention to the ways biblical texts and exegesis are reflected in euchological texts not only has the potential to provide clarity on how the early Christians related to the Bible in general and within their liturgical rites. It may also provide an additional source for answering questions about the dating and provenance of particular rites by identifying the overlap with strains of patristic exegesis, for which we possess significant evidence.